2010
DOI: 10.1161/circinterventions.110.946426
|View full text |Cite|
|
Sign up to set email alerts
|

Six-Month Results of the NEVO RES-ELUTION I (NEVO RES-I) Trial

Abstract: on behalf of the NEVO ResElution-I InvestigatorsBackground-Drug-eluting stents reduce restenosis and reintervention rates but are complicated by stent thrombosis, which may be related to polymer coating. The NEVO sirolimus-eluting coronary stent (NEVO SES) is designed to improve long-term percutaneous coronary intervention safety by combining sirolimus release from reservoirs with bioabsorbable polymer to reduce spatial and temporal polymer exposure. Methods and Results-NEVO ResElution-I was a prospective rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 31 publications
0
14
2
Order By: Relevance
“…In addition, the angiographic potency of the O-SES with an in-stent LLL of 0.10±0.32 mm at 9 months compares well with other new-generation DES. [21][22][23][24][25][26][27][28] The O-SES platform has several distinguishing characteristics. First, the strut thickness of the device is reduced to 60 μm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the angiographic potency of the O-SES with an in-stent LLL of 0.10±0.32 mm at 9 months compares well with other new-generation DES. [21][22][23][24][25][26][27][28] The O-SES platform has several distinguishing characteristics. First, the strut thickness of the device is reduced to 60 μm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Third, the antiproliferative drug used for drug release is the mammalian target of rapamycin inhibitor sirolimus. The drug is applied at a dose density of 1.4 μg/mm 2 , which corresponds well to the one previously used with the sirolimus-eluting Cypher and Nevo stent platforms, 27,30 and is released during a period of 3 months with 50% of drug released during the first 30 days. Fourth, the drug is released from a biodegradable poly-l lactic acid layer, which degrades into carbon dioxide and water.…”
Section: Discussionmentioning
confidence: 99%
“…Six-month followup period demonstrated that NEVO stent is superior to TAXUS Liberté stent. Stent thrombosis was not observed in the NEVO stent group (44).…”
Section: Sirolimus Eluting Stentsmentioning
confidence: 77%
“…These results matched those of the larger angiographic trial that demonstrated superiority of the NEVO SES over the TAXUS Liberté PES for the primary end point of in-stent late loss (0.13Ϯ0.31 mm versus0.36Ϯ0.48 mm, PϽ0.001 for noninferiority and superiority). 13 …”
Section: Discussionmentioning
confidence: 99%